2016
DOI: 10.21608/ejrs.2016.42067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Addition of Zinc Enriched Spirulina on Growth and Physiological Performance in Growing Rabbits.

Abstract: The present experiment was carried out to evaluate the effects of Zinc-enriched Spirulina (Zn-Sp) supplementation as an organic Zn source on the growth performance, nutrients digestibility, carcass characteristics, blood parameters and economic efficiency of growing rabbits. A total of forty eight male NZW rabbits (35 days old) were allotted to four groups (12 rabbits for each), 4 replicates (3 rabbits for each). Three levels of 75 and 100 mg Zn-Sp/kg diet) were compared to a control group without Zn-Sp add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Al-Sagheer et al [32], who found a significant rise in dressing percentage in rabbits fed dietary supplements containing Nano-ZnO at 100 mg/kg, with no differences in the ratios of the liver, kidneys, and heart to body weight when compared to the control group. Male rabbits' liver, kidney, and heart functions were unaffected by diets containing ZnO at a dosage of 100 mg/kg [33]. In comparison to the control group, dressing, liver, and kidney percentages in rabbits fed ZnO at doses of 50, 100, 200, and 400 mg/kg diet did not differ significantly [34], in line with our results.…”
Section: Discussionsupporting
confidence: 89%
“…Al-Sagheer et al [32], who found a significant rise in dressing percentage in rabbits fed dietary supplements containing Nano-ZnO at 100 mg/kg, with no differences in the ratios of the liver, kidneys, and heart to body weight when compared to the control group. Male rabbits' liver, kidney, and heart functions were unaffected by diets containing ZnO at a dosage of 100 mg/kg [33]. In comparison to the control group, dressing, liver, and kidney percentages in rabbits fed ZnO at doses of 50, 100, 200, and 400 mg/kg diet did not differ significantly [34], in line with our results.…”
Section: Discussionsupporting
confidence: 89%
“…The reduced fat content in the meat may be due to Zn being a cofactor in the biological function as a divalent cation primarily when bound to enzymes, other proteins and plays an essential protective role in the regulation of lipid accumulation and metabolism [ 40 ]. Amer et al [ 48 ] showed increased hot carcass weight, dressing, and total edible parts% in rabbits fed Zn supplemented diets at 50, 75, and 100 mg/kg compared with the control group. In contrast, Selim et al [ 34 ] reported no change in carcass traits in rabbits fed diets supplemented with a 50, 100, 200, or 400 mg zinc oxide /kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of Adel et al [26], who reported that substituting soybean meal with SP at 20, 40, and 60% in growing rabbit diets significantly enhanced digestibility of dry matter (DMD), organic matter (OMD), crud protein (CPD), and crud fiber (CFD), but digestibility of ether extract (EED) was unaffected. Also, Amer et al [27] found that increasing zinc-enriched SP in the rations of growing rabbits improved all nutrient digestibilities, except for CFD, which not affected. However, DalleZotte et al [28] stated that rabbits fed diets containing Spirulina, Thyme or a mixture had no effect on dry matter intake (DM), body weight, or nutrient digestibilities except for EED, which was recorded as significantly lower compared with rabbits fed the control diet.…”
Section: Discussionmentioning
confidence: 97%